2020
DOI: 10.1371/journal.pone.0227969
|View full text |Cite
|
Sign up to set email alerts
|

Opening gap width influences distal tibial rotation below the osteotomy site following open wedge high tibial osteotomy

Abstract: PurposeAlthough rotation of the distal portion of the tibia below the osteotomy site is considered an inevitable change in the axial plane in open wedge high tibial osteotomy (HTO), several studies on this issue have shown contradictory results. The purpose of this study was, therefore, to determine the direction and amount of distal tibial rotation following open wedge HTO using a three-dimensional reconstructed model. MethodsThis study involved 41 patients (42 knees) undergoing open wedge HTO for primary med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Clinically, Kim et al [8] found that the degree of DTR was not related to the amount of coronal correction after MOWHTO. Kim et al [15] reported that the correction angle was the only predictor of DTR, with a larger correction angle observed in the group with distal tibial rotation > 3° compared to the group with rotation ≤ 3°. Lee et al [17] found a positive correlation between the hinge axis angle and internal rotation of the distal tibia when the hinge axis was positioned more posterolaterally, while the gap ratio was negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, Kim et al [8] found that the degree of DTR was not related to the amount of coronal correction after MOWHTO. Kim et al [15] reported that the correction angle was the only predictor of DTR, with a larger correction angle observed in the group with distal tibial rotation > 3° compared to the group with rotation ≤ 3°. Lee et al [17] found a positive correlation between the hinge axis angle and internal rotation of the distal tibia when the hinge axis was positioned more posterolaterally, while the gap ratio was negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of relevant studies investigating the axial rotation of the distal tibia relative to the proximal tibia during MOWHTO, and the conclusions drawn from existing studies are controversial. Some studies have reported internal rotation, while others have reported external rotation of the distal tibia [9,10,[15][16][17]. Factors in uencing tibial rotation have also been reported, including tuberosity osteotomy angle [9,15], ange angle [16], hinge axis angle in axial plane [17] and correction angle [9,15,16], but a consensus has yet to be reached.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in KJLO after MOWHTO are usually less than the amount of change in the anatomical geometry of the proximal tibia (change in MPTA), which is a direct result of MOWHTO procedures [9, 10, 24]. A plausible explanation for the relative mitigation of increasing postoperative KJLO was the postoperative change of ankle valgus and hindfoot varus to restore neutral hip–knee–ankle coronal plane alignment [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the different management of these key structures around the knee joint during surgery might lead to various rotational changes after HTO. [13] In recent biomechanical research, Yazdi et al [24] reported that with 15˚ of external rotation for the distal tibia, the medial compartment contact pressure was decreased by 11% compared to that in the neutral position. However, in order to facilitate external tibial rotation, a tibia shaft and fibulectomy were simultaneously performed.…”
Section: Discussionmentioning
confidence: 99%